On the main financial predictors of credit default - Memić, Deni (Naše gospodarstvo, 2012)
The purpose of this paper is to investigate if any significant relationship exists between a wide set of financial ratios and the probability of credit default among the companies in the Federation of Bosnia and Herzegovina. Most existing literature in the field of credit default probability focuses on bond markets. Very few studies focus on credit default using bank loan data. To our knowledge, no such studies have been conducted and published covering data from Bosnia and Herzegovina. We found a significant relationship between the financial ratios and credit default probability. Return on assets (ROA) seems to be the most influential financial ratio on the probability of the credit default. We also found that other financial ratios have a significant influence on credit default, such as EBIDA-Replacement Capex and average account payable days. A broader study using similar data sets from companies in the Republic of Srpska as well as regional countries can be beneficial in assessing broader conclusions and possible similarities in credit default occurrence as well as the main variables affecting it. The similar data from the Republic of Srpska was unavailable for this study. The research results imply that banks may use the assessed model as an additional tool in risk management procedures when deciding whether to provide a new loan facility or not as well as in assessing the credit risk within the existing portfolio.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; podjetja; poslovne finance; nelikvidnost; kreditna sposobnost; banke; kreditiranje